PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV B SDS MUHAMMADIYAH KECAMATAN MANDAU - Yunita, Imna; Marhadi, Hendri; ', Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted because of the low results of fourth grade students learn science and SDS Muhammadiyah Mandau sub. Of the 25 students who achieve KKM many as 10 people (40%) while students who did not complete 15 (60%) with an average 60.tujuan research to Improve Learning Outcomes Science In Grade IVB SDS Muhammadiyah Mandau sub with the application of Quantum Learning Model teaching. The results obtained by the average value of the basic score of 60 increase in cycle 1 by 22.66% to 73.6. In cycle 11 value - average students also increased by 36.66% to 82. On the basis of completeness score IPA student learning outcomes is only 40% (not finished). After the professor of applied learning model Quantum Teaching in cycle 1 classical completeness increased to 64% (complete), the classical completeness 11 cycles obtained are increased increased to 92%. Activities of teachers at the first meeting 75% good category, increasing at a meeting of 2 to 83.3% with very good category. In the second cycle 1 meeting increased to 87.5% categorized very well, increasing to 95.8% at the confluence of two very good category. Activities of students in cycle 1 the first meeting activity students acquire a percentage of 70.8% in both categories. The second meeting of cycle 1 to be 79.6% in both categories. In cycle 11 the first meeting of student activity increased to 83.3% with very good category, and at the second meeting of the cycle 11 back increased to 95.8% with very good category. Key words : Quantum Teaching, Learning Outcomes IPA